Further Experiments On Buckling Of Cones With Imperfect Length Subjected To Axial Compression - Ifayefunmi, Olawale; Mahidan, Fairuz Mardhiah (Transstellar Journal Publications and Research Consultancy Private Limited (TJPRC), 2020)
The paper presents further experiments into the buckling of mild steel truncated cones having imperfect length subjected to axial compression. Two types of wave form imperfections with different number of waves along the compressed edge are considered in the current paper, and they are: (i) triangular waves, and (ii) square waves. Twenty-two (22) conical models (two perfect and twenty imperfect cones with axial imperfection amplitude, A, of 0.28) were manufactured in pairs from mild steel. Test results reveal good repeatability of experimental data. The errors within each pair vary from 0% to 4%. The buckling load of the cone is differently affected by wave imperfections shape. The results indicate that the wave shape strongly affect the buckling strength of conical shells. Also, it is shown that the buckling loads of tested cones are less sensitive when imperfection shape is triangular compared to their sensitivity under other imperfection shape